Improving the Competence of Pekapuran Raya Village Apparatus in Managing Maternal and Child Health Data: Peningkatan Kompetensi Perangkat Kelurahan Pekapuran Raya dalam Mengelola Data Kesehatan Ibu dan Anak - Anggraini, Dewi; Asmu’i, Asmu’i; Sukmawaty, Yuana; Maisarah, Maisarah; Maulida, Maisya; Sinambela, Talenta Parasian; Zaskia, Novia Ramadhani Putri; Situmorang, Amsal Halomoan; Cahyadi, Rizqa Nabiilah; Azkia, Shofia; Nurhaliza, Alya (Universitas Lancang Kuning, 2025)
This community service program has addressed data management challenges faced by Posyandu health workers in Pekapuran Raya Sub District, Banjarmasin City. The primary objective is to enhance digital data management capabilities among healthcare workers' through scientific and technical training using Microsoft Excel. The training was conducted at the Central Bureau of Statistics in Banjarmasin on September 3, 2024. Based on the collected data analysis from pre-test and post-test showed improvements in the three core competencies: data management ability (from 57.7% to 84.6%), data presentation capability (from 57.7% to 92.3%), and dashboard development skills (from 61.5% to 80.8%). Statistical analysis using the Wilcoxon test confirmed the significance of these improvements (p < 0.05). Furthermore, participants’ evaluation data analysis indicated that this program was highly effective, with 88.5% of participants reporting positive feedback on the training methodology, materials, and facilities. This intervention has effectively demonstrated the capacity of structured technology training to enhance community healthcare data management systems, especially for monitoring maternal and child health.